Pioneer biocrust communities prevent soil erosion in temperate forests after disturbances - Gall, Corinna; Nebel, Martin; Quandt, Dietmar; Scholten, Thomas; Seitz, Steffen (Biogeosciences, 2022)
Soil erosion continues to be one of the most serious environmental problems of our time and is exacerbated by progressive climate change. Until now, forests have been considered an ideal erosion control. However, even minor disturbances of the forest floor, for example, from heavy vehicles used for timber harvesting, can cause substantial sediment transport. An important countermeasure is the quick restoration of the uncovered soil surface by vegetation. To date, very little attention has been paid to the development of nonvascular plants, such as bryophytes, in disturbed areas of temperate forests and their impact on soil erosion. This study examined the natural succession of pioneer vegetation in skid trails on four soil substrates in a central European temperate forest and investigated their influence on soil erosion. For this purpose, rainfall simulations were conducted on small-scale runoff plots, and vegetation was continuously surveyed during the same period, primarily to map the development of bryophytes and the occurrence of biological soil crusts (biocrusts). Biocrusts appeared immediately after disturbance, consisting primarily of bryophyte protonemata and cyanobacteria as well as coccoid and filamentous algae that lost their biocrust characteristics as succession progressed. They were present from April to July 2019, with a particular expression in the skid trail that was on shale clay (Psilonotenton Formation) and silty clay loam substrate. In general, skid trails on clayey substrates showed considerably higher bryophyte cover and species richness. Although bryophytes were subsequently overtopped by vascular plants, they managed to coexist until their growth was restricted due to leaf litter fall. Brachythecium rutabulum and Oxyrrhynchium hians were the most important and persistent pioneer bryophyte species, while Dicranella schreberiana and Pohlia lutescens were volatile and quickly disappeared after spreading in the summer. Sediment discharge was 22 times higher on disturbed bare soil compared with undisturbed forest soil and showed the largest sediment removal in the wheel tracks. Counteracting this, soil erosion decreased with the recovery of surface vegetation and was particularly reduced with growing pioneer biocrusts in summer, but it again increased in winter, when vascular vegetation became dominant. This leads to the conclusion that the role of bryophyte-dominated biocrusts in forests has been underestimated so far, and they can contribute more to soil conservation at specific times of succession than vascular plants.